On the use of time-averaging restraints when deriving biomolecular structure from 3J-coupling values obtained from NMR experiments - Smith, L; van Gunsteren, W; Hansen, N (Springer Verlag, 2016)
Deriving molecular structure from 3J-couplings obtained from NMR experiments is a challenge due to (i) the uncertainty in the Karplus relation 3J(θ) connecting a 3J-coupling value to a torsional angle θ, (ii) the need to account for the averaging inherent to the measurement of 3J-couplings, and (iii) the sampling road blocks that may emerge due to the multiple-valuedness of the inverse function θ(3J) of the function 3J(θ). Ways to properly handle these issues in structure refinement of biomolecules are discussed and illustrated using the protein hen egg white lysozyme as example.